Assessing soil fertility index under different forest land cover - Dewi, Widyatmani Sih; Purwanto, Purwanto; Anisa, Siti Solikhatun; Hartati, Sri (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2024)
Soil fertility is often evaluated under various forest land cover types to determine the capacity of each area to support plant productivity. Therefore, this study aimed to (1) assess the current soil fertility status of six land cover types in the Alas Bromo educational forest of Universitas Sebelas Maret using the Soil Fertility Index method and (2) identify the factors influencing the status. The six different land cover types investigated in this descriptive-exploratory study using a survey method included (1) pine, (2) pine-mahogany, (3) mahogany, (4) mixed trees, (5) annual crops, and (6) pine replanting, with four repetitions. Furthermore, the composite soil sample represented each repetitive area, and the assessment results showed that the soil fertility status was categorized as low to moderate. The categorization order was mahogany>mixed trees>pine replanting>annual crops>pine>pine-mahogany which had fertility indices of 0.57, 0.56, 0.53, 0.51, 0.49, and 0.45, respectively. Soil fertility determinants across the six land cover types comprised litterfall, breast height diameter, and tree density. Future investigations should evaluate the relationship between litter quality, soil biota, and decomposition rate with fertility to identify the appropriate strategy for fertility enhancement on each land cover.